Proceedings of the 3rd Innovations in Theoretical Computer Science Conference 2012
DOI: 10.1145/2090236.2090246
|View full text |Cite
|
Sign up to set email alerts
|

Paging for multi-core shared caches

Abstract: Paging for multi-core processors extends the classical paging problem to a setting in which several processes simultaneously share the cache. Recently, Hassidim proposed a model for multi-core paging [25], studying cache eviction policies for multi-cores under the traditional competitive analysis metric and showing that LRU is not competitive against an offline policy that has the power to arbitrarily delay request sequences to its advantage. While Hassidim brought attention to this problem, an effective and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Katti and Ramachandran consider page replacement polices for multicore shared-cache environments [29]. Several authors have considered other aspects of paging where the size of internal memory or the pages themselves vary [2,25,27,32,33,46] e.g., because several processes share the same cache. For example, [32] considers a model where the application itself adjusts the cache-size, and [27,46] consider a model where the page sizes vary.…”
Section: Related Workmentioning
confidence: 99%
“…Katti and Ramachandran consider page replacement polices for multicore shared-cache environments [29]. Several authors have considered other aspects of paging where the size of internal memory or the pages themselves vary [2,25,27,32,33,46] e.g., because several processes share the same cache. For example, [32] considers a model where the application itself adjusts the cache-size, and [27,46] consider a model where the page sizes vary.…”
Section: Related Workmentioning
confidence: 99%
“…We refer to this type of interleaving as free interleaving. Hassidim [15] and Lopez-Ortiz and Salinger [18] considered free interleaving while analyzing cache replacement algorithms at the shared cache.…”
Section: Disjoint and Shared Memory Frameworkmentioning
confidence: 99%
“…Cache partitioning has emerged as a technique to increase run time predictability and increase performance on multi-core processors [8,14]. Theoretic research on online multi-core caching shows that the cache partition (which may be dynamic) has more influence on the performance than the eviction policy [5,12]. To obtain effective cache partitions, methods have been developed to estimate the running time of jobs as a function of allocated cache, that is the functions T j (x) (see for example the cache locking technique of [10]).…”
Section: Introductionmentioning
confidence: 99%
“…Related Work: Theoretic study of multi-core caching have shown that traditional online paging algorithms are not competitive in the multi-core scenario [5,12]. Both papers [5,12] show that the offline decision version of the caching problem is NP-complete, in slightly different models. Much of the difficulty in designing competitive online algorithms for multi-core caching stems from the fact that the way in which the request sequences of the different cores interleave is dependent on the algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation